Report of a ECPGR Task Force Meeting on a Beta core collection: Held at Cappelle-en-Pévèle (France) on 30 September, 2000 - International Board for Plant Genetic Resources (2000)
Report of the Task Force meeting on Beta core collection, 30 September 2000, Cappelle-en-Pévèle (France)